A Fast Optical Method for the Determination of Liquid Levels in Microplates. (18th June 2011) - Thurow, Kerstin; Stoll, Norbert; Ritterbusch, Kai
Abstract : Parallel liquid handling systems are widely used in different applications of life sciences. In order to avoid false positive or negative results which lead to higher costs due to the replication of the experiments it is necessary to monitor the process and success of liquid delivery. An easy method for the determination of the liquid levels in microplates has been developed and evaluated. The optical method bases on the measurement of the liquid level using CCD cameras followed by special algorithms for the evaluation and visualization of the measured data. The proposed method was tested in changing environmental lighting for two different liquids. These tests confirm our approach towards optical liquid level determination for smallest volumes in microplates and also show the challenges regarding environmental lighting and different physical properties of fluids.